Deleterious Effects of Hyperactivity of the Renin-Angiotensin System and Hypertension on the Course of Chemotherapy-Induced Heart Failure after Doxorubicin Administration: A Study in Ren-2 Transgenic Rat - Kala, Petr; Bartušková, Hana; Piťha, Jan; Vaňourková, Zdenka; Kikerlová, Soňa; Jíchová, Šárka; Melenovský, Vojtěch; Hošková, Lenka; Veselka, Josef; Kompanowska-Jezierska, Elzbieta; Sadowski, Janusz; Gawrys, Olga; et al. (International journal of molecular sciences, 2020)
Doxorubicin's (DOX) cardiotoxicity contributes to the development of chemotherapy-induced heart failure (HF) and new treatment strategies are in high demand. The aim of the present study was to characterize a DOX-induced model of HF in Ren-2 transgenic rats (TGR), those characterized by hypertension and hyperactivity of the renin-angiotensin-aldosterone system, and to compare the results with normotensive transgene-negative, Hannover Sprague-Dawley (HanSD) rats. DOX was administered for two weeks in a cumulative dose of 15 mg/kg. In HanSD rats DOX administration resulted in the development of an early phase of HF with the dominant symptom of bilateral cardiac atrophy demonstrable two weeks after the last DOX injection. In TGR, DOX caused substantial impairment of systolic function already at the end of the treatment, with further progression observed throughout the experiment. Additionally, two weeks after the termination of DOX treatment, TGR exhibited signs of HF characteristic for the transition stage between the compensated and decompensated phases of HF. In conclusion, we suggest that DOX-induced HF in TGR is a suitable model to study the pathophysiological aspects of chemotherapy-induced HF and to evaluate novel therapeutic strategies to combat this form of HF, which are urgently needed.
Keywords: Animals; Doxorubicin; Female; ženské pohlaví; Heart Failure; Renin; kardiotoxicita; srdeční selhání; renin-angiotensin systém; Antineoplastic Agents; protinádorové látky; Renin-Angiotensin System; krevní tlak; Rats, Sprague-Dawley; chemotherapy-induced heart failure; potkani Sprague-Dawley; doxorubicin; krysa rodu Rattus; hypertension; zvířata; renin-angiotensin-aldosterone system; Blood Pressure; renin; Rats; Cardiotoxicity